The Theological Implications of the Council’s Liturgical Constitution: Changes in the Concept of the Sacrament of Anointing of the Sick - Ignacy Różycki (Studia Theologica Varsaviensia)
The Theological Implications of the Council’s Liturgical Constitution: Changes in the Concept of the Sacrament of Anointing of the Sick.